Citra Dialog Antara Agama Dalam Persfektif Islam dan Kristian : Analisis Awal - Najtama, Fikra (Tasamuh: Jurnal Studi Islam, 2015)
This paper aims to expound religious dialogue from the historical perspective in looking into its scenario. In apprehending a form of perspective on the concept of interfaith dialogue, the viewpoint of Islam and Christian are referred to. An early stage of analysis is done in order to comprehend to what extend does the new paradigm introduced by the Christian dialoguers influence the religious dialogue. This writing also demonstrates religious dialogue in Malaysia from the perspective of Muslim and Christian scholars. Besides, this paper discovers that the interfaith dialogue scenario in Malaysia has its own distinguished perspective as it is deeply embedded with revelation and is relevant in the current plural society